Harvest impacts on caribou population dynamics in South West Greenland - Witting, Lars; Cuyler, Christine (Rangifer, 2011)
We examined the effects of hunting on caribou populations in South West Greenland from year 1999 to 2007. In the Ameralik area a reported average annual harvest of 2950 caribou coincided with a population decline from 31 000 (90% CI: 22 000 - 44 000) animals in 1999 to 8900 (90% CI: 5800 - 13 000) in 2007. A survey estimate from 2006 indicates that a suggested target caribou density of 1.2 / km2 was met. A Bayesian population model estimates the annual replacement for Ameralik at minus 170 individuals (90% CI: -550 - 460), which indicates that the target density may or may not be maintained even in the total absence of a hunt. For the Qeqertarsuatsiaat area an average annual harvest of 230 caribou appears to have left the density unaffected, remaining steady on target with an abundance of approximately 5000 individuals. The harvest in this area increased from 100 animals in 2000 to 440 in 2006. With an estimated 2007 replacement of 190 (90% CI: -190- 960) caribou per year the target density may not be maintained in the future unless hunting restrictions are implemented. The density of caribou in Qeqertarsuatsiaat may, however, be maintained over the short term if the emigration of animals from Ameralik into Qeqertarsuatsiaat continues.